Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1601-5223.1997.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Alcohol Dehydrogenase Genes in Alcoholic and Nonalcoholic Individuals from Valencia (Spain)

Abstract: Polymorphisms in the two variable ADH loci (ADH2 and ADH3) were analyzed in two groups (alcoholics and nonalcoholics) from a Spanish population. The frequencies were similar to those reported for other Causcasian groups. ADH2-1 and ADH3-1 genotypes were more frequent in alcoholics than in nonalcoholics, but the differences were not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…The studies report conflicting findings with no correlation [11,36,37,38], protection against alcohol dependence [8,10] or inconclusive results [39,40]. In contrast to our study, Borras et al [8] and Espinos et al [11] found that the ADH1C * 1 allele was more frequent in alcohol-dependent patients compared to that of non-drinkers in Europeans. Similarly, Cichoz-Lach et al [10] showed that the ADH1C * 1 allele and ADH1C * 1/ * 1 genotype were detected significantly more frequently in the alcohol-dependent group than in the control group.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The studies report conflicting findings with no correlation [11,36,37,38], protection against alcohol dependence [8,10] or inconclusive results [39,40]. In contrast to our study, Borras et al [8] and Espinos et al [11] found that the ADH1C * 1 allele was more frequent in alcohol-dependent patients compared to that of non-drinkers in Europeans. Similarly, Cichoz-Lach et al [10] showed that the ADH1C * 1 allele and ADH1C * 1/ * 1 genotype were detected significantly more frequently in the alcohol-dependent group than in the control group.…”
Section: Discussioncontrasting
confidence: 50%
“…Among these, a functional relevance of the ADH1C genetic polymorphisms that appear to impact on ethanol metabolism and susceptibility to alcoholism has been reported [7]. Its role in the development of alcohol dependence differs according to ethnicity [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. Furthermore, small studies have generated somewhat inconsistent results, especially in populations where the minor allele frequency is low, which would serve to reduce statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Borras at al. (3) and Espinos et al (22), who studied Europeans, found that the ADH1C*1 allele was more frequent in alcohol-dependent subjects than among non-drinkers. Similarly, the results of the present study show that the ADH1C*1 allele and ADH1C*1/*1 genotype were detected significantly more frequently in the alcohol-dependent group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding ADH1C*1 among whites are more contradictory and show ambiguous findings: no correlation (13,22,23), protection against alcohol dependence (3) or inconclusive results (24,25). Borras at al.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies in alcoholism 28,33,38,39,44,56,65,66 and two studies in liver disease 33,44 reported that the controls were age-or sex-matched. Studies were conducted in various populations of racial background: 24 involved Caucasians, 5 …”
Section: Eligible Studiesmentioning
confidence: 99%